Κεντητός επιτάφιος της Κοκκώνας του Ιωάννου στη Θεσσαλονίκη - Παζαράς Νίκος; Δουλγκέρη Ευπραξία (Μακεδονικά, 2011)
The Art Gallery of Mrs Anait Kalphagian at Thessaloniki acquired inthe year 2006 an embroidered Epitaphios from the «Galerie NeumeisterMünchener Kunstauktionhaus» of Munich. This «supreme veil», as TheodoreStuditis called it, is embroidered on red silk and represents, as usual, the Lamentation of Christ. Its down edge border is filled in with a dedicatory inscription, which includes the name of the female embroiderer «Kokkona touIoannou». This artisan’s only other so far known work had been a sanctuarypyle of the year 1747, encountered in the Panahrantou Monastery at the island of Andros. The scene of the epitaphios combines elements of the so called «liturgical» and «narrative - historical» type: the symbolic representation of the sacrificed Lamb with the angelic hosts and the Lamentation with all the usualmourning figures. Some of the works’ most striking features are the perfectbalance and monumentality of the composition, the idealised figures, the highquality of design and the harmonious palette of colours. Byzantine style isblended with slight Western influences, especially in the portraits and clothing of some figures, as well as the rules of perspective. The embroidery hasbeen worked in relief, mainly with fine gold and silver threads, while partslike hands and faces are mostly stitched in brown, black and wheat-colouredthreads and silks.All in all, the epitaphios of Thessaloniki is associated by its high qualityin iconography, style and technique with a group of earlier epitaphioi, fabricated by famous Constantinopolitan workshops at the end of 17th – beginningof the 18th century, like those headed by Despoineta and Mariora. All thesemasterpieces prove that the art of gold embroidery flourished anew in Constantinople in the so called «Phanariote» period, which approximately datesfrom 1680 until 1780.